Experiential interprofessional education for medical students at a regional medical campus - Laura Walmsley (Canadian Medical Education Journal, 2018)
Background: Regional medical campuses are often challenged with providing effective interprofessional education (IPE) opportunities for medical students that are comparable to those at main campuses. At distributed teaching sites, there is often less IPE infrastructure and fewer learners of other health professions. On the other hand, distributed medical education (DME) settings often have community-based clinical environments and fewer medical students, which can provide unique opportunities for IPE curriculum innovation. Methods: At the Niagara Regional Campus (NRC) of McMaster University, the Horizontal Elective for Interprofessional Growth & Healthcare Team ENhancement (HEIGHTEN) was developed to provide first-year medical students the opportunity to learn from and work alongside nurses in a community hospital. This study assesses HEIGHTEN’s impact on students’ knowledge, confidence, and attitudes towards interprofessional care, as well as student satisfaction with the learning experience using a mixed methods evaluation. Results: Findings suggest that HEIGHTEN provided an enjoyable learning experience, fostered positive interprofessional attitudes and an appreciation for the nursing role. Voluntary participation by medical students was high and increased both within the regional campus and with students from other campuses travelling to participate. Conclusion: This model for IPE can be feasibly replicated by distributed teaching sites to provide medical students with hands-on, experiential learning early in training, leading to positive attitudes and behaviours supporting interprofessional collaboration (IPC).